Mapping Chemical Hazards in Animal Food Origin Product for Food Safety Teaching Materials - Nova Kurnia; Kholik Kholik; Khaeruman Khaeruman (Postgraduate, University of Mataram, 2023)
Animal origin food product is quite vulnerable to the threat of chemical hazards. Mapping potential chemical hazards is needed to establish good and safe food handling methods. In addition, the mapping can be used as the basis for the preparation of food safety teaching materials that have not been available so far. The purpose of this study is to map various potential chemical hazards in food of animal origin food product to be used as teaching materials for food safety. This research is included as a literature study by collecting various types of scientific references that outline potential chemical hazards that can threaten animal origin food product. The results showed potential chemical hazards in the form of antibiotic residues in beef, chicken, and eggs; excess nitrates and nitrites in beef; scombrotoxin in cob fish; pesticides and heavy metals in honey; and formalin and borax in chicken meat and fish. The results of mapping the potential chemical hazards of animal origin food product can then be used to compile food safety teaching materials